Anosmia-related internet search and the course of the first wave of the COVID-19 pandemic in the United States. Issue 12 (December 2021) - Madden, Kenneth M.; Feldman, Boris
Abstract: Background: The current pandemic of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) was first reported in Wuhan, China. Although the first case in the United States was reported on Jan 20, 2020 in Washington, the early pandemic time course is uncertain. One approach with the potential to provide more insight into this time course is the examination of search activity. This study analyzed US search data prior to the first press release of anosmia as an early symptom (March 20, 2020). Methods: Daily internet search query data was obtained from Google Trends (September 20th to March 20th for 2015 to 2020) both for the United States and on a state-by-state basis. Normalized anosmia-related search activity for the years prior to the pandemic was averaged to obtain a baseline level. Cross-correlations were performed to determine the time-lag between changes in search activity and SARS-CoV-2 cases/deaths. Results: Only New York showed both significant increases in anosmia-related terms during the pandemic year as well as a significant lag (6 days) between increases in search activity and the number of cases/deaths attributed to SARS-CoV-2. Conclusions: There is no evidence from search activity to suggest earlier spread of SARS-CoV-2 than has been previously reported. The increase in anosmia-related searches preceded increases in SARS-CoV-2 cases/deaths by 6 days, but this was only significant over the background noise of searches for other reasons in the setting of a very large outbreak (New York in the spring of 2020). Highlights: Recent work has suggested using digital epidemiology to follow pandemics. In our view, these previous studies have several methodological errors. They used correlations long after anosmia symptoms were well documented in the media. We demonstrated significant issues with digital surveillance during such a high interest event. A large signal is required to overcome noise introduced by searches for other reasons. Abstract : COVID-19, Infodemiology, Internet search.